Influence of stand density on growth and water use efficiency in Eucalyptus clones - Hakamada, Rodrigo Eiji; Hubbard, Robert M.; Moreira, Gabriela Gonçalves; Stape, Jose Luiz [UNESP]; Campoe, Otavio; Ferraz, Silvio Frosini de Barros (Elsevier, 2020)
We examined the influence of stand density and genotype on transpiration and water use efficiency in high productivity plantations. Three widely planted Eucalyptus clones that differ in drought tolerance and productivity (E. urophylla, E. urophylla × E. grandis and E. grandis × E. camaldulensis, clones IP, B2 and C3, respectively) were measured at four densities (590, 1030, 1420, and 2950 trees ha−1). Over the 1-year study period (1.5–2.5 years after planting), individual biomass increment decreased with increasing density, from 21 kg tree−1 at 590 trees ha−1 to 6 kg tree−1 at 2950 trees ha−1. Stand increment typically follows the reverse pattern, increasing as density increases. This was the case for two clones (IP and B2), but stand increment was consistent across tree spacings for C3. Transpiration increased with density, from a low of 622 mm yr−1 to a high of 879 mm y−1. Some of the increased water use resulted from higher leaf area index at higher densities. The B2 clone transpired the most water on average, produced the greatest increment (23 Mg ha−1 yr−1 for 1030 trees ha−1), and produced the most wood L−1 transpiration (water use efficiency, 2.3 g biomass L−1). The clone C3 had the lowest increment (only 12 Mg ha−1 yr−1) because of the combination of low transpiration and low water use efficiency (only 1.5 g biomass L−1). Optimizing clone selection and silviculture for the combination of high yield and high water use efficiency may help reduce risks from drought as well as water conservation.
Keywords: Clonal plantations; Planting density; Stocking; Transpiration; Water use efficiency